1991
DOI: 10.1523/jneurosci.11-12-03695.1991
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glucocorticoid secretion by the hippocampal formation in the primate

Abstract: Inhibition of the adrenocortical axis by glucocorticoids (GCs) occurs at both hypothalamic and suprahypothalamic sites. In the rat, the hippocampus has been shown to be an essential suprahypothalamic site. The present study shows that the hippocampal system serves a similar role in the nonhuman primate. Bilateral lesions that included the hippocampal formation and the parahippocampal cortex; the hippocampal formation, parahippocampal cortex, and the amygdala; or the fornix all produced GC hypersecretion in cyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
2
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(66 citation statements)
references
References 29 publications
1
60
2
3
Order By: Relevance
“…Almost 40 years ago, excessive cortisol secretion during depression was first reported (Gibbons and McHugh, 1962). Hypercortisolism and insensitivity to feedback suppression during depression have been extensively investigated to determine the relative contributions of adrenal hypersensitivity to ACTH (Amsterdam et al, 1989), pituitary resistance to GC feedback (Holsboer et al, 1987), pituitary hypersensitivity to CRF and other hormones (Gold et al, 1984), and resistance at the hippocampus (Sapolsky et al, 1991;Young et al, 1991). Although we do not have cortisol levels from previous depressive episodes, many of our subjects had histories of hospitalization, ECT treatment, and multiple episodes, indicating relatively more severe major depression, a predictor of elevated cortisol and dexamethasone suppression test nonsuppression (Whiteford et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 40 years ago, excessive cortisol secretion during depression was first reported (Gibbons and McHugh, 1962). Hypercortisolism and insensitivity to feedback suppression during depression have been extensively investigated to determine the relative contributions of adrenal hypersensitivity to ACTH (Amsterdam et al, 1989), pituitary resistance to GC feedback (Holsboer et al, 1987), pituitary hypersensitivity to CRF and other hormones (Gold et al, 1984), and resistance at the hippocampus (Sapolsky et al, 1991;Young et al, 1991). Although we do not have cortisol levels from previous depressive episodes, many of our subjects had histories of hospitalization, ECT treatment, and multiple episodes, indicating relatively more severe major depression, a predictor of elevated cortisol and dexamethasone suppression test nonsuppression (Whiteford et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, patients with or without lesions of the hippocampus, which is known to exert an inhibitory action on this neuroendocrine regulation, 28 did not differ in regard to response of the HPA axis.…”
mentioning
confidence: 84%
“…It is possible that the lack of hypersecretion in the hippocampal group reflected functional recovery after surgery caused by plasticity in the HPA axis or suprahypothalamic control systems (Jacobson and Sapolsky et al, 1991) and that disinhibition of corticosterone secretion would be expressed at shorter intervals between lesion and test. In the above experiments, recovery intervals varied between 10 and 29 d. It is possible that these intervals were too long to detect a possible effect on adrenocortical hyperactivity.…”
Section: Effect Of Recovery After Surgerymentioning
confidence: 99%
“…Physiological evidence from various sources indicates that hippocampal activity exerts an inhibitory influence on the HPA axis (Jacobson and , but does normal HPA activity depend on this hippocampal input or can other control systems provide similar inhibition? Several studies have shown that damage to the hippocampus increases basal glucocorticoid secretion (Fendler et al, 1961;Kim and Kim, 1961;Knigge, 1961;Moberg et al, 1971;Fischette et al, 1980;Wilson et al, 1980;Sapolsky et al, 1984Sapolsky et al, , 1991Herman et al, 1989), but these lesions were made either by aspiration or by transection of the fimbria-fornix and caused damage to bypassing fibers as well as adjacent brain systems, including the parahippocampal cortices and several subcortical structures. Other studies failed to identify a hippocampal inhibitory influence on the HPA axis (Coover et al, 1971;Lanier et al, 1975;Conforti and Feldman, 1976;Smotherman et al, 1981;Bradbury et al, 1993;Herman et al, 1995) but there was only incomplete damage to the hippocampus in these studies.…”
Section: Introductionmentioning
confidence: 99%